Advanced control of turbofan engines - Richter, Hanz (Springer New York, 2012)
Advanced Control of Turbofan Engines describes the operational performance requirements of turbofan (commercial)engines from a controls systems perspective, covering industry-standard methods and research-edge advances. This book allows the reader to design controllers and produce realistic simulations using public-domain software like CMAPSS: Commercial Modular Aero-Propulsion System Simulation, whose versions are released to the public by NASA. The scope of the book is centered on the design of thrust controllers for both steady flight and transient maneuvers. Classical control theory is not dwelled on, but instead an introduction to general undergraduate control techniques is provided. This book also: Develops a thorough understanding of the challenges associated with engine operability from a control systems perspective, describing performance demands and operational constraints into the framework and language of modern control theory Presents solid theoretical support for classical and advanced engine control concepts,  including new analyses of the min-max selector systems frequently used in commercial engine control systems Has a bottom-up, progressive approach establishing a unified framework for the analysis of classical and advanced engine control schemes, with a strong design orientation Provides detailed coverage of advanced techniques such as adaptive control, sliding mode control and model predictive control as applied to gas turbine engines. Covers public-domain, high-fidelity simulation resources, allowing the reader to reproduce the simulations of the book and to develop a basis for independent controller benchmarking studies Advanced Control of Turbofan Engines is an ideal book for aerospace or mechanical engineers with basic knowledge in control systems, control engineers unfamiliar with gas turbines, and first year graduate students in mechanical, electrical, or aerospace engineering.